Effects of Seasonal Factors in The Goats’ Reproductive Efficiency - Usman Mir Khan; Ali Murad Khan; Umar Murad Khan; Zeliha Selamoğlu (Turkish Journal of Agriculture: Food Science and Technology)
Interest in goat farming is at its peak since the last decade of 20th century because the role of goat is well established in animal protein as well as in economic uplift of poor masses in the tropics and subtropics, but also constitutes an important component of traditional farming systems. Goat is a better option as farm animal in the tropics and subtropics as it can withstand dehydration and has better browsing habit which enables it to survive where cattle and sheep farming is difficult. Reproductive performance of does is of immense importance as contributing factor towards increased meat production and in finding out more prolific animals. This is the main factor affecting productivity of goats. Therefore, an improved reproduction rate will be an approach to increase in numbers. Reproductive seasonality represents a natural adaptation that provides important advantages for birth and offspring survival and development, as lambing/kidding coincides with good weather and maximum availability of forage. It is believed that photoperiod is the environmental factor other than food availability that determines the sexual activity in sheep and goat. This review paper focuses on the general aspects of seasonal factors influencing the goat’s reproductive efficiency.